Infrastructures, population dynamics and internal migrations in Sub-Saharan Africa - (:unkn) unknown (My University, 2022)
Sub-Saharan Africa is one of the regions of the world that faces the greatest current and future challenges in population and development due to the demographic dynamics observed and the most difficult climatic conditions. In 2050, the African population is estimated to be more than two billion and will represent a quarter of the world population. The empirical works in this thesis analyze the interactions between population dynamics, infrastructures, and internal migrations in two sub-Saharan African countries by mobilizing original longitudinal demographic data and panel data relatively rare in an African context. Chapter 1 examines the causal effect of a sharp increase in school construction between 1998 and 2005 on fertility, early marriage, and reproductive health behavior in the Niakhar Health and Demographic Surveillance System (HDSS) in rural Senegal. The Niakhar HDSS data were matched with geo-referenced and dated school data, allowing us to identify women exposed and not exposed to the expansion of school supply. The results show that exposed women are more likely to complete primary school and have fewer children before the age 25 than unexposed women. A delay in the age at marriage and health behavior change related to childbirth location appear to be the mechanisms at work. Delivering less at home lowers the risk of infant mortality which prevents mothers to engage in a catch-up fertility strategy. However, exposure to schools does not seem to affect health behavior related to prenatal visits. Chapter 2 investigates the impact of rainfall shocks on infant mortality in rural Senegal over three decades (1985-2016) by merging geo-referenced rainfall data and the Niakhar HDSS data. A positive deviation of rainfall from the historical mean increases the post-neonatal mortality rate during the period 1985-2016 with a strong effect in the rainy season suggesting a disease-environment effect. Analyzing the heterogeneity of the impact of rainfall b
Keywords: African Research